IMPLEMENTATION OF SURAH AL-A'RAF VERSES 56-58 AS THE SUSTAINABLE LIFESTYLE BASED ON ECOSUFISM PARADIGM - Meliyana, Fitria Susan; Putra, Aqiel Sifa' Abdallah (Al-Munir: Jurnal Studi Ilmu Al-Qur'an dan Tafsir, 2024)
The indifference of the Muslim community to nature is due to the dichotomy of the meaning of worship with social life. The community feels that environmental cleanliness is not their full responsibility, so a new paradigm concept is needed that realizes that ecology is part of life and activities in protecting nature, including a form of love for God. This research comes with the aim of finding the concept of a sustainable lifestyle with the paradigm of ecosufism contained in Surah Al-A'raf verses 56-58. The research method used is a qualitative method with literature study techniques. In the previous research, it concluded that Nasr offers a concept of human ethical take care of nature properly in the form of issuing the concept of ecosufism, so it will create a harmony between God, nature, and humans. As a development of the results of previous research, this study provides contextual practices as an implementation of the interpretation of verses and the concept of ecosufism in the form of the concept of cleanliness as part of faith, the concept of the human life cycle, the concept of the benefits of life, the concept of asceticism, and the concept of living with nature that can be done in everyday life without having to move away from the "afterlife".